Game Based Learning: Alternative 21st Century Innovative Learning Models in Improving Student Learning Activeness - Aryanti Dwi Untari (Department of Tadris IPS FITK IAIN Syekh Nurjati Cirebon, 2022)
Abstract: This study aims to provide alternative solutions for 21st century learning innovations in increasing student learning activity. Where the 21st century requires students to have skills and critical thinking skills, communication, collaboration, and creativity. Relevant learning to increase student learning activity is learning that is based on constructivist understanding through a student-centered learning approach, one of which is the game-based learning model. The research method used in this research is descriptive qualitative research method. The data collected in this study include: observation results, interview results, documentation, and field notes. Data analysis refers to analytical techniques according to Miles, Huberman & Saldana (2014), namely using four stages of data analysis, namely data collection, data reduction, data presentation, and data verification or drawing conclusions. The results of this study indicate that the use of game-based learning models as innovative learning models of the 21st century provides a major role in increasing student learning activity. The potential for using games that can be integrated into the learning process is enormous. The activeness of student learning by using the game-based learning model applied in class X MAS Al-Khairiyah Pipitan Serang can be seen from the active involvement of students in the game, the courage to answer questions, express opinions, and meet the challenges of the game by collaborating with their team groups, being involved in activities solving problems both individually and in groups, constructing understanding independently, and reflecting on the learning activities that have been implemented. Based on these findings it can be understood that integrating games into a learning process through game-based learning is able to prepare students to face the challenges and skills needs of the 21st century.Keywords: Game Based Learning, Learning Innovation, 21st Century Learning Abstrak: Penelitian ini bertujuan untuk memberikan solusi alternatif inovasi pembelajaran abad 21 dalam meningkatkan keaktifan belajar siswa. Dimana abad 21 menuntut peserta didik untuk memiliki kecakapan dan keterampilan critical thinking, communication, colaboration, dan creativity. Pembelajaran yang relevan untuk meningkatkan keaktifan belajar siswa ialah pembelajaran yang dilandasi oleh paham konstruktivistik melalui pendekatan student centred learning salah satunya ialah model pembelajaran game based learning. Metode penelitian yang digunakan dalam penelitian ini ialah metode penelitian kualitatif deskriptif. Data yang dikumpulkan dalam penelitian ini meliputi: hasil observasi, hasil wawancara, dokumentasi, dan catatan lapangan. Analisis data mengacu pada teknik analisis menurut Miles, Huberman & Saldana (2014) yakni menggunakan empat tahap analisis data yaitu pengumpulan data, reduksi data, penyajian data, dan verifikasi data atau penarikan kesimpulan. Hasil penelitian ini menunjukan bahwa Penggunaan model pembelajaran game based learning sebagai model pembelajaran inovatif abad 21 memberikan peran besar dalam meningkatkan keaktifan belajar siswa. Potensi pemanfaatan game yang dapat diintegrasikan ke dalam proses pembelajaran sangatlah besar. Keaktifan belajar siswa dengan menggunakan model pembelajaan game based learning yang diterapkan di kelas X MAS Al-Khairiyah Pipitan Serang dapat dilihat dari keterlibatan aktif siswa dalam permainan, keberanian menjawab pertanyaan, mengemukakan pendapat, dan memenuhi tantangan permainan dengan berkolaborasi bersama tim kelompoknya, terlibat dalam kegiatan pemecahan masalah baik secara invidu maupun kelompok, mengkontruksi pemahaman secara mandiri, dan merefleksi kegiatan pembelajaran yang telah dilaksanakan.Berdasarkan temuan ini dapat dipahami bahwa mengintegrasikan permainan dalam sebuah proses pembelajaran melalui game based learning mampu menyiapkan peserta didik menghadapi tantangan dan kebutuhan keterampilan abad 21.Keywords: Game Based Learning, Inovasi Pembelajaran, Pembelajaran abad 21